Lynching in the West, 1850-1935 - Gonzales-Day, Ken (John Hope Franklin Center Book., 2006)
Accounts of lynching in the United States have primarily focused on violence against African Americans in the South. Ken Gonzales-Day reveals racially motivated lynching as a more widespread practice. His research uncovered 350 instances of lynching that occurred in the state of California between 1850 and 1935. The majority were perpetrated against Latinos, Native Americans, and Asian Americans; more Latinos were lynched in California than were persons of any other race or ethnicity. An artist and writer, Gonzales-Day began this study by photographing lynching sites in order to document the absences and empty spaces that are emblematic of the forgotten history of lynching in the West. Drawing on newspaper articles, periodicals, court records, historical photographs, and souvenir postcards, he attempted to reconstruct the circumstances surrounding the lynchings that had occurred in the spaces he was photographing. The result is an unprecedented textual and visual record of a largely unacknowledged manifestation of racial violence in the United States. Including sixteen color illustrations, "Lynching in the West" juxtaposes Gonzales-Day's evocative contemporary photographs of lynching sites with dozens of historical images. Gonzales-Day examines California's history of lynching in relation to the spectrum of extra-legal vigilantism common during the nineteenth century--from vigilante committees to lynch mobs--and in relation to race-based theories of criminality. He explores the role of visual culture as well, reflecting on lynching as spectacle and the development of lynching photography. Seeking to explain why the history of lynching in the West has been obscured until now, Gonzales-Day points to popular misconceptions of frontier justice as race-neutral and to the role of the anti-lynching movement in shaping the historical record of lynching in the United States